Sociology of personal life - May, Vanessa (London : Bloomsbury, 2021)
Vanessa May$1 (Bs Sociology of Personal Life is a pioneering text that skillfully links personal experiences with broader societal structures. Through a detailed examination of everyday life, May reveals how personal choices both influence and are influenced by the social environment. Her adept use of theoretical frameworks alongside practical examples provides a new lens for understanding the relationship between the personal and the public. The book covers a range of topics, including friendship, family, consumerism, and technology, challenging readers to rethink their assumptions about personal experiences. Although the book's primary focus on Western societies may limit its global applicability, it remains an invaluable resource for students, researchers, and anyone interested in the intricate dynamics of contemporary life.s
Includes glossary, bibliographical references (p. 189-210) and index.
Keywords: Family and Intimacy; Consumerism and Identity; Personal life in sociology; Friendship and social networks:.; Personal choices and social structure